Male Majority, Female Majority, or Gender Diversity in Organizations: How Do Proportions Affect Gender Stereotyping and Women Leaders’ Well-Being? - Steffens, Melanie C.; Viladot, Maria Angels; Scheifele, Carolin (Frontiers in Psychology, 2019)
Whereas popular wisdom often centers on character differences between women and men when explaining work-related behavior, Kanter (1977) predicted that the proportion of women and men present is the crucial factor: With unequal proportions, women (and other minority persons) are singled out as “tokens” and gender becomes salient, which has been theorized to have a range of negative consequences. In contrast, if proportions of women and men are similar (i.e., in the presence of gender diversity), gender is not salient, and the work environment becomes much more positive for women. These considerations imply that not only a male majority, but also a female majority at work has negative consequences, because gender becomes salient in both cases. However, empirical research on work environments with female majorities at the top of organizations is scarce. The present study tested the perception of a range of negative consequences, including work-related well-being, among women in leadership positions in Spain who reported a male majority, a female majority, or similar proportions of both genders at the top level of the organization. The online sample consisted of a total of N = 649 women leaders. In addition to work-related well-being, we measured perceived work-family conflict, perceived feelings of guilt among other women, traditional gender stereotypes regarding warmth and competence, women-leadership stereotypes, negative work-related stereotypes of mothers, gender harassment, and stigma consciousness. Almost all of our findings support Kanter’s theorizing that equal proportions of both genders go along with more positive perceptions than a male majority does. A female majority went along with as negative perceptions as a male majority regarding several of the outcome variables, but was associated with the most positive perceptions for other outcomes. We discuss possible reasons for these mixed findings.